(untitled) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-3-43-57 This research is devoted to the study of emotive vocabulary in modern Spanish-language and English-language mass media. Application of methods of contextual, stylistic and semantic analysis, methods of quantitative calculation and continuous sampling, emotion classifications by K. Izard and V.I. Shakhovsky in a step-by-step analysis of language means expressing emotions in analyzed texts in English and Spanish allow us to talk about the predominance of negative emotions in the articles. In publications in Spanish and English, texts on politics, economics, football, coronavirus and ecology have the highest emotionality. The specifics of expressing emotions in newspaper texts turned out to be directly related to the national characters of the Spaniards and the British. Key words: verbalization of emotions; the linguistics of emotions; linguoculturology; press; emotive; emotion; emotivity